(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
A 60 years old lady, a diagnosed case of hypertension and hypothyroidism, admitted in CMH Dhaka with the complaints of high grade continuous fever, headache, vomiting and lower abdominal pain following total hysterectomy about two weeks back. On general and physical examination, she was found febrile, mildly anaemic, pitting oedema over both legs and erythematous skin rash over face, trunk and extremities. Relevant laboratory investigations were done including bone marrow aspiration which revealed haemophagocytic lymphohistiocytosis. Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 89-90